Rantai Pasokan Dalam Strategi Sektor Wisata Kabupaten Karawang Untuk Meningkatkan Pendapatan Asli Daerah: Rantai Pasokan - Ihsan Nasihin; Rieke Retnosary (Politeknik Ganesha Medan, 2023)
Karawang Regency has quite a number of tourist destinations that can be visited by local and foreign tourists (foreign tourists). With so many tourists visiting, it will have a positive impact on the region as local revenue (PAD) or gross domestic product (GDP) and has a target of being able to increase benefits for the community, one of which is increasing job opportunities for local residents. The research method that will be used in this study is a qualitative method with an interpretive research paradigm and a case study approach, in obtaining data using interviews, observation and documentation. Data analysis that will be used in this study is triangulation using primary data and secondary data. The results of this study are that the Karawang Regency government can implement and develop the tourism sector supply chain with the Pentahelix concept, where the Pentahelix concept has three developments, namely the first accessibility related to access to tourist destination locations, the second amenity functions to maintain and improve facilities and infrastructure in the tourist destination environment, and the three attractions that focus on activities or new rides in tourist areas